2007
DOI: 10.1159/000101400
|View full text |Cite
|
Sign up to set email alerts
|

Possible Novel Receptor for PGD<sub>2</sub> on Human Bronchial Epithelial Cells

Abstract: Prostaglandin D2 (PGD2), a major prostanoid produced by activated mast cells, has long been implicated in allergic diseases. Recent studies have shown that PGD2 exerts its effects through two different G-protein-coupled receptors (GPCRs), the D-prostanoid receptor (DP) and the chemoattractant receptor-homologous molecule expressed on T helper type-2 cells (CRTH2), expressed in various human tissues. The PGD2/CRTH2 system mediates the chemotaxis of eosinophils, basoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The epithelial cell acts as a first line of defense against harmful components in cigarette smoke, and DP2 is expressed on human bronchial epithelial cells (Chiba et al, 2006;Sargent et al, 2009). Intracellular expression of DP2 was demonstrated in NCI-H292 and normal human bronchial epithelial cells by both reverse transcription-polymerase chain reaction and flow cytometry (Chiba et al, 2007). The functional implications of DP2 expression on this cell type have yet to be fully elucidated; however, our data suggest that the efficacy of DP2 antagonists on cigarette smoke-induced pulmonary inflammation and mucus hypersecretion may be due to the direct effect of the DP2 antagonist on the epithelial cells, although, as stated above, a role for the DP2-neutrophil-epithelial cell axis cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial cell acts as a first line of defense against harmful components in cigarette smoke, and DP2 is expressed on human bronchial epithelial cells (Chiba et al, 2006;Sargent et al, 2009). Intracellular expression of DP2 was demonstrated in NCI-H292 and normal human bronchial epithelial cells by both reverse transcription-polymerase chain reaction and flow cytometry (Chiba et al, 2007). The functional implications of DP2 expression on this cell type have yet to be fully elucidated; however, our data suggest that the efficacy of DP2 antagonists on cigarette smoke-induced pulmonary inflammation and mucus hypersecretion may be due to the direct effect of the DP2 antagonist on the epithelial cells, although, as stated above, a role for the DP2-neutrophil-epithelial cell axis cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“… 34 We found that DP2 was expressed on epithelial cells within biopsy specimens from asthmatic patients. Although previous publications have described the expression of DP2 on cultured normal human epithelial cells and H292 cells, 35 our report is the first to demonstrate the in vivo expression of DP2 on epithelial cells within bronchial biopsy specimens. A recent report has described expression of DP2 on epithelial cells in lung volume reduction tissue from patients with COPD, 17 but whether this expression was associated with disease severity was not investigated because no healthy control tissue was included.…”
Section: Discussionmentioning
confidence: 51%
“… 39 In our study DP2 was found to have intracellular and extracellular expression on epithelial cells similar to that seen in previous studies for this receptor. 14,35 DP2 activation caused functional consequences on epithelial cells that were likely mediated through cell-surface receptors. However, intracellular receptor activation can also occur, as has been reported for other G protein–coupled receptors, 40 and its functional importance requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…It is released into the airway following an antigen challenge during an acute allergic response [30]. PGD 2 induces chemotaxis of Th2 cells, eosinophils, and basophils as a consequence of the activation of its receptors [31]. This suggests that PGD 2 promotes inflammation in allergic asthma.…”
Section: Airway Inflammatory Effect Through Ahr Activation In Asthmentioning
confidence: 99%